Investigating pathways for agricultural innovation at scale: Case studies from Brazil - Chiodi Bachion, L.; Barcellos Antoniazzi, L.; Rocha Junior, A.; Chamma, A.; Barretto, A.; Safanelli, J.L.; Araújo, M.; Takahashi, N.; Maule, R.; Martins, S.; Ranieri, S.; Alves, V. (Commission on Sustainable Agriculture Intensification, 2022)
This is one of three country studies on Innovation Pathways in Agri-food Systems, managed by the Commission for Sustainable Agriculture Intensification (CoSAI). The three studies use a common analytical framework to generate lessons on factors leading to successful innovation pathways, to guide future investment.